Reduction of Photoautotrophic Productivity in the Cyanobacterium Synechocystis sp. Strain PCC 6803 by Phycobilisome Antenna Truncation - Page, Lawrence E. (American Society for Microbiology, 2012)
Truncation of the algal light-harvesting antenna is expected to enhance photosynthetic productivity. The wild type and three mutant strains of Synechocystis sp. strain 6803 with a progressively smaller phycobilisome antenna were examined under different light and CO(2) conditions. Surprisingly, such antenna truncation resulted in decreased whole-culture productivity for this cyanobacterium.